Botryoidal hematite from the Schwarzwald (Germany): heterogeneous uranium distributions and their bearing on the helium dating method - Wernicke, Rolf Stephan; Lippolt, Hans J. (Earth and planetary science letters, 1993)
Neutron-induced fission tracks of small grain mounts of two co-genetic botryoidal hematites (Eisenbach hematite-manganese mineralization district, Mittelschwarzwald, Germany) reveal substantial heterogeneous235U distributions.235U fission tracks in the three shells of one hematite yield total uranium concentrations of 26, 48 and 160 ppm (2σerrors of approximately20%), respectively. The other hematite consists of a coherent mineralogical unit devoid of shell-type features, in which four localities have been probed with a range in total uranium between 26 and 600 ppm. Induced fission tracks from a larger section of the single unit hematite show a subparallel arrangement of five well-defined235U zones with densities ranging from about 106 tracks/cm2 in zone 5 to approximately25 × 106 tracks/cm2 in zone 2. Additionally, in zones 3-5 gradual internal track density variations of over 100% can be recognized. A traverse shows that there is an overall decrease in radioactivity from zone 1 to zone 5. An autoradiograph confirms the existence of five zones with different activities and allows correlation of the high-activity zone 2 with a 0.5 mm thin internal hematite micro-layer. Analyses by mass spectrometer of the triple-shell hematite, resulted in the following concentrations: 26, 45 and 166 ppm uranium (2σerrors of1%) and 0.55-3.25 μl/g4He (2σerrors of3%). The four probed localities in the single unit hematite show smaller variations at 40-73 ppm uranium (2σerrors of0.5%) and 0.75-1.37 μl/g4He (2σerrors of3%). α-spectrometry of thorium yields values in the 1-5 ppm range for both hematites. The uranium and4He concentration differences measured allow construction of two internal (U, Th)-He isochrons yielding identical ages (2σerror) of156 ± 1 Ma and155 ± 6 Ma. Concordance of both isochrons in our opinion is strong evidence for a geologically significant age. We interpret the data as emplacement ages. Further, we suggest that botryoidal hematite has the potential to be a prolific chronometer for the helium method on Mesozoic hematite-bearing mineralizations.